Pediculosis and Factors Affecting its Prevalence among Schoolchildren in Amol City, Northern Iran - Zohreh Gholami; Mohammad Saaid Dayer; Amrollah Azarm (Tehran University of Medical Sciences, 2024)
Background: Head louse infestation, pediculosis, is a serious health problem worldwide. Infected children usually suffer from itching, allergies, and secondary infections besides psychological disorders such as depression and lack of self-confidence leading to school failure. This study aimed to investigate the status of pediculosis and its determinant factors among schoolchildren in Amol City, Northern Iran. Methods: This study included 228 schools frequented by about 20017 students. Pediculosis was determined by careful examination of students' hair on the scalp, back of the neck, and around the ears. The diagnosis was based on observation of live adults, nymphs, and nits. A questionnaire was used to record the personal and demographic characteristics of participants. Results: This study revealed that the prevalence of pediculosis among schoolchildren during all schooling seasons (autumn, winter, and spring) correlated with sex: the prevalence being higher among girls than boys (p= 0.00). In addition, the highest rates of pediculosis occurred during the autumn season (p= 0.00). The public schools accommodated higher numbers of louse-infected students than the private ones (p= 0.00). While head louse occurred at higher frequencies in long hair over the schooling year, dandruff had anti-louse effects (p= 0.00) during cold seasons, autumn, and winter. Socioeconomic status and educational level of parents played determinant roles in head louse prevalence (p= 0.00). Schoolchildren coming from socioeconomically well-situated families had lower rates of head louse infestation. Conclusion: Our results showed that head pediculosis was a serious health problem among schoolchildren in Amol city and its prevalence and severity tended to be multifactorial.